EFFECT OF CRYSTALLINITY TO OVERPOTENTIAL ON Ni₃Fe ALLOY AS ELECTROCATALYST IN HYDROGEN EVOLUTION REACTION - Qonita Mu'minah; Achmad Rochliadi; Aep Patah (Jurnal Sains Materi Indonesia, 2020)
EFFECT OF CRYSTALLINITY TO OVERPOTENTIAL ON Ni3Fe ALLOY AS ELECTROCATALYST IN HYDROGEN EVOLUTION REACTION. Ni-Fe alloys can be used as electrocatalyst for the hydrogen evolution reaction (HER) in an alkaline solution. HER consumed highly energy and overpotential driven. The overpotential value corresponding to the electron transfer in reaction can be affected either by metal combination or alloy as a cathode. Ni₃Fe  alloy had been successfully synthesized by the electrodeposition method using direct-current (DC) on a 304 L type stainless steel substrate. The modified Watts bath deposition was used NiCl2·6H2O and FeCl3·6H2O as precursors of the alloy. The optimum conditions of the reaction were obtained at pH of the solution is 2.20±0.02 with 25 mA/cm² current density at 55 °C for 160 minutes. Ni₃Fe alloy was characterized by Powder X-ray Diffraction (PXRD), Energy-Dispersive X-ray Spectroscopy (EDX), and Scanning Electron Microscopy (SEM). The electrocatalytic property of Ni3Fe alloy was electrochemically measured in 1 M KOH solution by polarization method using a Tafel plot with a scanning rate of 1 mV/s. As a result, the mass ratio of Ni²+ /Fe³+ in bath deposition influenced the electrocatalytic property of Ni₃Fe alloy. Ni₃Fe alloy with a higher crystallinity lowered the overpotential value of HER up to 67% compared to Ni metal.